The Relationship between Exclusive Breastfeeding and the Incidence of Acute Respiratory Tract Infection in Children Under Five in Muna Regency Southeast Sulawesi Province - Yusnani, Yusnani; Saafi, La Ode; Umi Nurlila, Ratna (Magister Kesehatan Universitas Mandala Waluya, 2024)
Backgrounds: Data obtained from the Muna District Health Service shows that there are still many toddlers affected by acute respiratory infections and each year this increases. In 2019 there were 3778 cases (23.7%), in 2020 there were 2500 cases (12.2%), while in 2021 there were 3868 cases (24.2%). The aim of this research is to analyze the relationship between giving exclusive breast milk and the incidence of acute respiratory infections in toddlers in Muna Regency, Southeast Sulawesi Province. Methods: This type of research is quantitative observational using a Cross Sectional Study design. This research was carried out in July 2022. The research population was all toddlers in Muna Regency, totaling 3868 people and a sample of 97 people obtained using proportional simple random sampling. Data were processed using the chi-square test, closeness test and phi test. Results: The research results showed that the results of the chi-square test on the variable giving exclusive breast milk obtained a p value of 0.000. This shows that H0 is rejected and Ha is accepted, meaning that there is a moderate relationship between exclusive breastfeeding and the eventAcute respiratory infectionsamong toddlers in Muna Regency, Southeast Sulawesi Province. Conclusion: There is a connection between giving exclusive breast milk and the incident Acute respiratory infectionsamong toddlers in Muna Regency, Southeast Sulawesi Province. It is hoped that mothers can provide knowledge about the factors related to the occurrence of acute respiratory infections in toddlers.